2008
DOI: 10.1104/pp.107.109363
|View full text |Cite
|
Sign up to set email alerts
|

Elongation Changes of Exploratory and Root Hair Systems Induced by Aminocyclopropane Carboxylic Acid and Aminoethoxyvinylglycine Affect Nitrate Uptake andBnNrt2.1andBnNrt1.1Transporter Gene Expression in Oilseed Rape

Abstract: Ethylene is a plant hormone that plays a major role in the elongation of both exploratory and root hair systems. Here, we demonstrate in Brassica napus seedlings that treatments with the ethylene precursor, aminocyclopropane carboxylic acid (ACC) and the ethylene biosynthesis inhibitor, aminoethoxyvinylglycine (AVG), cause modification of the dynamic processes of primary root and root hair elongation in a dose-dependent way. Moreover, restoration of root elongation in AVG-treated seedlings by 1 mM L-glutamate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
71
1
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(83 citation statements)
references
References 69 publications
9
71
1
2
Order By: Relevance
“…[38][39][40][41] In contrast, Leblanc et al 42 have shown that N uptake and nitrate transporter BnNrt2.1 transcript levels were markedly reduced in the presence of ethylene promoter in Brassica napus, but were increased in the presence of ethylene inhibitor. Li et al 43 have observed inhibition of ACS expression in the presence of SA in Lycopersicon esculentum.…”
Section: Discussionmentioning
confidence: 84%
“…[38][39][40][41] In contrast, Leblanc et al 42 have shown that N uptake and nitrate transporter BnNrt2.1 transcript levels were markedly reduced in the presence of ethylene promoter in Brassica napus, but were increased in the presence of ethylene inhibitor. Li et al 43 have observed inhibition of ACS expression in the presence of SA in Lycopersicon esculentum.…”
Section: Discussionmentioning
confidence: 84%
“…Leblanc et al (2008) showed that treatment of oilseed rape seedlings with ACC and AVG reduced and enhanced nitrate uptake, respectively, by monitoring 15 N uptake. They suggested that a posttranscriptional regulation of nitrate transporters may be involved in the regulation of nitrate transport by ethylene (Leblanc et al , 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Inhibited cotton root growth (Armstrong and Drew 2002) reduced plasma membrane H + -ATPase activity, impaired nutrient acquisition, and higher 1-aminocyclopropene-1-carboxlic acid (ACC) in root tissues inhibited root growth Fig. 2 Waterlogging-induced aerenchyma formation in rice (a) and wheat (b) (Mustroph and Albrecht, 2003), while they are absent in cotton (c) (Conaty et al 2008) waterlogging Oxygen (Leblanc et al 2008) (Fig. 4).…”
Section: Waterloggingmentioning
confidence: 92%